2022
DOI: 10.1038/s41598-022-19990-z
|View full text |Cite
|
Sign up to set email alerts
|

A plethora of ocular surface manifestations in a multidisciplinary ocular graft-versus-host disease unit

Abstract: To describe the experience in a recently created ocular graft-versus-host disease unit in a tertiary hospital and to detail ocular surface features and complications after allogeneic hematopoietic stem cell transplantation (allo-HSCT). This retrospective study included all patients who underwent allo-HSCT, with or without chronic GVHD and were being monitored in the Hematopoietic Stem Cell Transplantation Unit in the UNICAMP Clinical Hospital (Campinas, Sao Paulo, Brazil) from 2015 to 2020. Patients were conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…One was Ocular Surface Disease Index (OSDI), which measures three aspects (the frequency of dry eye symptoms, visual impact of dry eye, and triggers) to denote the severity of dry eye. Higher scores usually indicate greater severity [26][27] . The other questionnaire was the QOL scale for Chinese patients with visual impairment (SQOL-DV1), which has 20 questions assessing symptoms, visual function, physical function, social activity, and psychology.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…One was Ocular Surface Disease Index (OSDI), which measures three aspects (the frequency of dry eye symptoms, visual impact of dry eye, and triggers) to denote the severity of dry eye. Higher scores usually indicate greater severity [26][27] . The other questionnaire was the QOL scale for Chinese patients with visual impairment (SQOL-DV1), which has 20 questions assessing symptoms, visual function, physical function, social activity, and psychology.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…35 Meibography images obtained at baseline and 1-year post-HSCT revealed an 80% meibomian gland dropout, with 19% of cases with persistent dropout despite treatment. 37 In another study, Trindade et al 38 reported a significant difference in the prevalence of conjunctival scarring, MGD, corneal opacity, and corneal neovascularization in post-HSCT patients with and without oGVHD.…”
Section: Clinical Manifestationsmentioning
confidence: 97%
“…1 b) bis hin zu einem Narbenentropium kommen [10 -13]. Im Rahmen der Keratoconjunctivitis siccaund insbesondere der Entzündung der Augenoberfläche durch aktivierte T-Zellen und dendritische Zellenfinden sich oft auch eine Chemose und lidkantenparallele konjunktivale Falten (LIPCOF) [13,14]. Das Spektrum der Hornhautveränderungen reicht von einer Keratopathia punctata superficialis (▶ Abb.…”
Section: Klinische Befundeunclassified
“…1 b) right up to a scar entropion [10 -13]. In the context of keratoconjunctivitis siccaand particularly inflammation of the ocular surface caused by activated T cells and dendritic cellschemosis and lid-parallel conjunctival folds (LIPCOF) are also often found [13,14]. The spectrum of corneal changes ranges from superficial punctate keratopathy (▶ Fig.…”
Section: Clinical Findingsmentioning
confidence: 99%